2013
DOI: 10.3389/fgene.2013.00219
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and epigenetics of arrhythmia and heart failure

Abstract: Heart failure (HF) is the end stage of several pathological cardiac conditions including myocardial infarction, cardiac hypertrophy and hypertension. Various molecular and cellular mechanisms are involved in the development of HF. At the molecular level, the onset of HF is associated with reprogramming of gene expression, including downregulation of the alpha-myosin heavy chain (α-MHC) gene and sarcoplasmic reticulum Ca 2+ ATPase genes and reactivation of specific fetal cardiac genes such as atrial natriuretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 164 publications
(211 reference statements)
1
47
0
Order By: Relevance
“…35,36 A recent study by Rangel et al demonstrated an interaction between DNA methylation and the ACE I/D polymorphism. 37 The DD genotype was found to be associated with a decrease in DNA methylation, which was associated with higher ACE activity.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 A recent study by Rangel et al demonstrated an interaction between DNA methylation and the ACE I/D polymorphism. 37 The DD genotype was found to be associated with a decrease in DNA methylation, which was associated with higher ACE activity.…”
Section: Discussionmentioning
confidence: 99%
“…HCN2 and HCN4 channels are present in the sinus node and regulate the pacemaker current I f and heart rate [1,4,7]. Abnormalities in HCN channels are also associated with MI-induced tachycardia [51]. Connexin 43 is a basic component of the gap junction and is involved in mediating electrical and chemical signals between cardiomyocytes in the cardiac conduction system and working cardiac muscle (atrium and ventricle) [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Altered miRNA signature risk of CV death [32][33][34][35][36][37] . Whether interactions between features of transcriptomics, proteomics and metabolomics are specifically for HFrEF and HFpEF remains still not clear.…”
Section: Histone Acetylationmentioning
confidence: 99%